An Argentine military-historical place of memory around the monument of General San Martín - Mugione Méndez, Macarena Gisela (Revista de historia., 2024)
In 1862, the inauguration of the commemorative monument in honor of General José de San Martín determined the creation and definition of one of the oldest squares in the city of Buenos Aires located in the current neighborhood of La Recoleta. The arrival of the monument consecrated this place as a site to commemorate and remember the armies of independence and all the military heroes of the nation, since, in 1990, the government decided that it was also pertinent to erect a Cenotaph to those who fell in the Malvinas. This article raises the idea that, with the installation of the statue of the liberator, the Plaza San Martín was configured over the centuries as a place of historical-military memory consolidated, from the officers, by the military events, the buildings that surround the square and the monuments located there.